Changes in unemployment rates and their spatial variations in Libya: A geographical analytical study - Al-Hamali, Mohamed Ibrahim ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2025)
The study presents a geographical analysis of unemployment rates and their spatial disparities in Libya. It focuses on the growth of the working-age population (15-64 years) from 910,000 in 1973 to 4.4 million in 2020 (63.8% of the population), along with an increase in the youth demographic (15-34 years) by 37.9%. The economically active population rose from 423,000 to 2.3 million, while the number of job seekers increased from 15,000 to 354,000, reflecting a change rate of 22.18%. The economic participation rate climbed from 36.6% to 48.8%, with women constituting 47.8% of job seekers. The age group (25-34 years) emerged as the most actively seeking employment, accounting for 48.3%. High school graduates recorded the highest unemployment rate (28.4%), and the overall unemployment rate rose from 3.6% in 1973 to 18.7% in 2023, with the highest rate in Ghat (24%) and the lowest in Al Jabal Al Akhdar (6.8%). The (25-34 years) age group registered the highest general unemployment rate (32.1%), with males in the same group at 39% and females (15-24 years) at 39.2%. The study recommended bolstering the private sector to reduce unemployment, as lower rates were observed with an increase in private-sector employment